Assumptions, Types of Accounting Manipulations and Their Application - Bachtijeva, Diana (Buhalterinės apskaitos teorija ir praktika, 2021)
The article describes the bonus plan, debt/equity and political cost hypotheses, based on a positive accounting theory, with reference to opportunistic approach, explaining the reasons for choosing accounting methods. Research based on these hypotheses has revealed the main types of financial information manipulation - earnings management and creative accounting. After conducting the analysis of scientific sources, the article presents the definitions of earnings management and creative accounting of various authors, distinguishes the types of earnings management – accrual-based earnings management and real earnings management. After analyzing the manipulation methods indicated in the literature, a comprehensive list of profit management and creative accounting methods are presented. The methods are structured and classified according to their compliance with accounting standards, types of profit management and their impact on accounting areas. The provided list and classification of methods is useful in a scientific sense for further research on this phenomenon.
Keywords: earnings mangement; creative accounting